2013
DOI: 10.1186/1471-230x-13-126
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: High expression level and nuclear localization of Sam68 are associated with progression and poor prognosis in colorectal cancer

Abstract: BackgroundSrc-associated in mitosis (Sam68; 68 kDa) has been implicated in the oncogenesis and progression of several human cancers. The aim of this study was to investigate the clinicopathologic significance of Sam68 expression and its subcellular localization in colorectal cancer (CRC).MethodsSam68 expression was examined in CRC cell lines, nine matched CRC tissues and adjacent noncancerous tissues using reverse transcription (RT)-PCR, quantitative RT-PCR and Western blotting. Sam68 protein expression and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…It has been reported that high expression of Sam68 is a is a predictor of poor prognosis in non-small cell lung cancer, oral tongue cancer, early-stage cervical cancer and colorectal cancer (8,9,13,14). In the present study, the expression level of Sam68 was demonstrated to be higher in NB tissues compared with their matched adjacent normal tissues.…”
Section: Discussionsupporting
confidence: 53%
“…It has been reported that high expression of Sam68 is a is a predictor of poor prognosis in non-small cell lung cancer, oral tongue cancer, early-stage cervical cancer and colorectal cancer (8,9,13,14). In the present study, the expression level of Sam68 was demonstrated to be higher in NB tissues compared with their matched adjacent normal tissues.…”
Section: Discussionsupporting
confidence: 53%
“…It was found that Sam68 could induce cervical cancer lymph node metastasis, which served as predictors of pelvic lymph node metastasis in cervical cancer patients [25]. In the colorectal cancer tissues, Sam68 was also elevated, and the high Sam68 expression level was significantly correlated with the characteristics of aggressive colorectal cancer [26]. The similar result was found in renal cell carcinoma [23].…”
Section: Discussionsupporting
confidence: 52%
“…Elevation in Sam68 protein levels has been proposed as a prognostic marker in multiple cancers (Chen et al, 2012; Liao et al, 2013; Song et al, 2010; Zhang et al, 2009), although the exact function of Sam68 in these cancers remains obscure. We recently revealed that Sam68 plays a crucial role in controlling DNA damage-induced PARP1 activation and PAR production; hence Sam68 deficiency dramatically dampens the PAR-dependent NF-κB signaling and DNA repair pathways initiated by DNA damage (Fu et al, 2016; Sun et al, 2016).…”
Section: Discussionmentioning
confidence: 99%